2006
DOI: 10.1097/01.shk.0000228171.32587.a1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Leukoreduced Blood Transfusion on Infection Risk Following Injury

Abstract: Allogeneic blood transfusions in surgical patients have been associated with an increased risk of infectious complications and organ dysfunction. Residual leukocytes contaminating units of packed red blood cells have been incriminated through the induction of anergy and/or a potentiated inflammatory response, leading to the possibility that leukoreduced red blood cell transfusion might mitigate these effects. We set out to evaluate the effect of leukoreduced red cell transfusion on the risk of infections compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 33 publications
1
107
1
1
Order By: Relevance
“…However, despite considerable theoretical advantages, clinical benefits of leukoreduction have been inconsistent in observational studies [39][40][41] and randomized trials. [42][43][44] In our study, later year of hospital admission was not associated with improved outcomes. However, our dataset is underpowered to examine the effect of leukoreduction specifically, since relatively few patients (*20%) were included in the post-leukoreduction period.…”
Section: Discussionmentioning
confidence: 58%
“…However, despite considerable theoretical advantages, clinical benefits of leukoreduction have been inconsistent in observational studies [39][40][41] and randomized trials. [42][43][44] In our study, later year of hospital admission was not associated with improved outcomes. However, our dataset is underpowered to examine the effect of leukoreduction specifically, since relatively few patients (*20%) were included in the post-leukoreduction period.…”
Section: Discussionmentioning
confidence: 58%
“…However, a subsequent meta-analysis of before-and-after studies did not show any effect of leukoreduction on postoperative infection or mortality, after adjusting for confounding factors (73). In trauma patients, before-and-after cohort studies have shown decreased rates of nosocomial infection and ARDS (74,75), but randomized clinical trials have shown no effect of leukoreduction on these outcomes (76,77).…”
Section: Management Of Anemia In Critical Illness Blood Transfusionsmentioning
confidence: 99%
“…These studies included singleand multicenter designs, clinical diagnosis, methods for documenting and reporting infections, and the proportion of transfused patients (range: 14%-95%). Among them, 5 included patients undergoing colorectal or gastrointestinal surgery [40][41][42][43][44], 1 was performed with patients undergoing aortic aneurysm repair or resection of gastrointestinal malignancy [45], and 1 included trauma patients [46]. The postoperative infection results in these RCTs, which were conducted with different patient populations using different study designs, are inconsistent.…”
Section: The Clinical Effects Of Allogeneic Leukocytes In Cardiac Surmentioning
confidence: 99%
“…In total, 13 RCTs on leukodepleted blood transfusions in different clinical settings evaluated postoperative infections as a primary or secondary endpoint [31][32][33][34][35][36][40][41][42][43][44][45][46]. These studies included singleand multicenter designs, clinical diagnosis, methods for documenting and reporting infections, and the proportion of transfused patients (range: 14%-95%).…”
Section: The Clinical Effects Of Allogeneic Leukocytes In Cardiac Surmentioning
confidence: 99%